Design and development of an intelligent battery charger station - Teoh, Weee Wee (Universiti Sains Malaysia, 2009)
This thesis presents the design and development of an intelligent battery charger for simultaneous charging of four NiMH batteries. It is designed to satisfy the demands of high current and fast charge applications such as electrical vehicles which use batteries as the electrical source energy. The purpose of this design is to provide an efficient charging algorithm using a microcontroller PIC16F877 in order to protect against overcharging and reduce the recharging time. This design includes the discharging function. In this design, the control and supervision of the whole charging process is entrusted to a microcontroller, which able to find out the initial battery state , decide the fit way to charge the battery (in order to ensure a long cycle-life) and determine when the charge process must be finished. The proposed design provides multiple charging current options with automated selection of optimum charging rate for the battery being charged. The charging algorithm is programmed in the PIC16F877 by using PIC Basic Pro. There are four basic charging algorithm used in this charger: slow (10%C), soft (20%C), fast (55%C) and trickle (4%C). The experimental results obtained show that the charger is functioning properly with the state defined in the microcontroller. The current regulation is successfully done by using PWM control. The accurate termination of fast charging cycle and safe charging of batteries demonstrate the reliable functioning of the proposed design. The charging and discharging curve obtained is almost the same as stated in the theoretical characteristic. The charging time to charge the battery from empty to full is almost two hours. The battery voltage at the end of charging cycle obtained is around 1.38V/battery. The fast charge cycle bring the battery to approximately 90% of the full charge condition. The implementation of design’s objective is fulfilled and is supported by experimental results.